Tomografía ultrasónica computarizada con esfuerzo medicamentoso en el caballo - Pidal, G. (2007)
The diagnosis of the cardiovascular diseases in the horse is simple when the failures are evident and are present at rest. That situation is complicated when the dysfunction is sub clinic and only evident during exercise. With the purpose to evaluate the global and regional inotropic behavior of the left ventricular myocardium the authors develop a test of Ultrasonic Computerized Tomography (UCT) with pharmacological drug effort in the horse. They propose as drug protocol the association of atropine sulphate (15?g/Kg) and dobutamina hidrocloride (in growing dose of 3 ?g/Kg/min, 6 ?g/Kg/min and 9 ?g/Kg/min) with step administration until reaching a stable cardiac rate above the 100 beats per minute. The capture and synchronization of images was carried out with an specifi c software, complemented with T-mode echocardiography measurements (at rest and during the maximum effort) of the following parameters: Diastolic and systolic thickness of interventricular septum; Diastolic and systolic thickness of the left ventricular free wall, Diastolic and systolic left ventricular diameter and Fractional shortening.